Bikes or burden - Kemp, Hans (Visionary Word Ltd, 2013)
In Vietnam the motorbike is the main mode of transport, not only for people but for every imaginable and unimaginable product and produce. Without the motorbike the economy would come to a halt. Bikes of Burden shows in 148 stunning, full color photographs how the motorbikes, the drivers and their loads ride around the cities and countryside in acts that defy your wildest imagination.